KOMPETENSI KEPRIBADIAN GURU DALAM PENGUATAN INTERAKSI SOSIAL DI MAN 1 JOMBANG - Kamilah, Intan; Brata, Diah Puji Nali (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Teacher personality competence is a competency related to the behavior of the teacher's personality that has noble values and is a role model for students. However, there are teachers who sometimes lack exemplary attitudes and behaviors that make students less respectful and make teachers as role models. The purpose of this study is to describe (1) forms of social interaction, (2) teacher personality competence, and (3) teacher personality competence in strengthening social interaction. The method used in this research is qualitative research. Data collection techniques through observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and conclusions. The results showed that (1) forms of social interaction, namely associative and dissociative (2) teacher personality competencies, namely acting in accordance with religious, legal, social and Indonesian national cultural norms, presenting themselves as honest, noble, and role models for students and society, presenting themselves as stable, mature, wise and authoritative, stable, mature, wise and authoritative, showing work ethic, high responsibility, pride in being a teacher and self-confidence, and upholding the code of ethics of the teaching profession and (3) teacher personality competence in strengthening social interactions, namely through fair behavior, polite behavior, communication, cooperation, and accommodation. The conclusion of this study is that there are forms of social interaction in the MAN 1 Jombang environment, one of which is cooperation. The personality competence of teachers at MAN 1 Jombang is having an authoritative, wise, and noble personality. Teacher personality competence in strengthening social interactions in the MAN 1 Jombang environment, one of which is polite behavior and communication.